2018
DOI: 10.1002/slct.201801527
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a New Siderophore Acinetoamonabactin Produced by a Salt‐Tolerant Bacterium Acinetobacter Soli

Abstract: A halotolerant bacterium Acinetobacter soli (MTCC 5918), isolated from the salt farm of our institute, was found to secrete a novel siderophore under iron deprivation conditions. A combination of multinuclear one and two dimensional NMR spectroscopies in conjunction with mass technique revealed that the siderophore, we named acinetoamonabactin (1), is a triscatechol derivative of tris(aminomethyl)methylamine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…Siderophore production. Siderophore production ability was tested based on the CAS agar analytical method [ 23 ]. The bacterial suspension during logarithmic growth period was centrifuged, and then re-suspended with distilled water.…”
Section: Methodsmentioning
confidence: 99%
“…Siderophore production. Siderophore production ability was tested based on the CAS agar analytical method [ 23 ]. The bacterial suspension during logarithmic growth period was centrifuged, and then re-suspended with distilled water.…”
Section: Methodsmentioning
confidence: 99%
“…This repetition indicates a focused research interest in employing E. coli as a model organism for studying the synthesis and secretion of siderophores, alongside efforts to identify new siderophore compounds. Notable contributions include Mudhulkar et al research on siderophores produced by halotolerant bacteria [92] and Oliveira et al's study on siderophore synthesis by Streptococcus mutans [93]. The analysis also highlighted these keywords' significant betweenness centrality, reflecting their pivotal role in connecting various research themes within the field.…”
Section: Analysis Of Research Hotspotsmentioning
confidence: 99%
“…Among the biosynthetic enzymes for vibriobactin, the amide synthase VibH showed highly flexible substrate specificity and was capable of transferring activated dihydroxybenzoate (DHB) to diverse acceptor amines in a model of a reconstituted synthetic pathway in Escherichia coli [ 77 ]. Acinetobacter species are able to produce polyamine-based catechol siderophores that are natural analogs of vibriobactins [ 78 , 79 ]. In particular, Reitz et al identified that the strain Acinetobacter bouvetii DSM 14964 can synthesize propanochelin, butanochelin and pentanochelin ( Table 1 ).…”
Section: Precursor-directed Biosynthesismentioning
confidence: 99%